2020
DOI: 10.21470/1678-9741-2019-0327
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Effects of Bretschneider’s HTK Solution and Cold Blood Cardioplegia on Systemic Endothelial Functions in Patients who Undergo Coronary Artery Bypass Surgery: a Prospective Randomized and Controlled Trial

Abstract: Coronary fistulas are rare anomalies that can affect approximately 1% of the population, presenting few specific symptoms, and are often found occasionally in coronary angiography. Here we describe the case of a 61-year-old patient with complaints of precordialgia and dyspnea since adolescence, with late diagnosis of coronary fistulas with drainage to the pulmonary artery, and with unsuccessful percutaneous treatment. Therefore, she underwent open surgery for the correction of the already known fistulas, in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…This article updates the previous meta-analysis Reynolds et al 2020 (26), with four added RCTs [ 16 , 17 , 23 , 25 ]. Our findings were consistent with the previous ones to a large extent.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This article updates the previous meta-analysis Reynolds et al 2020 (26), with four added RCTs [ 16 , 17 , 23 , 25 ]. Our findings were consistent with the previous ones to a large extent.…”
Section: Discussionsupporting
confidence: 64%
“…Another 31 articles were excluded by full-text screening. Finally, 12 trials [ 6 , 10 , 16 25 ] were included in our qualitative and quantitative synthesis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with previous work, the fabricated CPB system in this study included several improvements, but inevitably had limitations. Previous studies have found that adding the CO 2 flush procedure contribute to a reduction of gaseous microemboli in CPB devices and corresponding improved neuropsychological outcomes [14,25,26]. Thus, we implemented the CO 2 flush procedure before surgery in our modified CPB system.…”
Section: Discussionmentioning
confidence: 99%
“…Bretschneider, describing the benefits of every component in his newly devised cardioplegia, mentioned lower concentrations of prime electrolytes (Na + , K + , and Ca 2+ ) compared with other cardioplegias [ 53 ]. By comparison, the hyperkalemic solution interferes in the production of the endothelium-derived relaxing factor, alters myocardial perfusion, and induces smooth muscle proliferation [ 54 , 55 ]. Moreover, in a study conducted by Ilker M. et al, the authors analyzed endothelial injury secondary to Bretschneider infusion versus cold blood cardioplegia in 50 CABG interventions.…”
Section: Bretschneidermentioning
confidence: 99%